Proposing an adapted visibility analysis methodology for the building height codes of the Shiraz development plan. (October 2020) - Mohseni, Farnaz; Lotfi, Sahand; Sholeh, Mahsa
Highlights: This paper has proposed a methodology of Visibility Analysis of development plans on strategic views. The proposed method has the advantage of less subjective evaluation due to its systematic and quantitative calculations. This research suggests legally preventative measures regarding urban development. Having the non-detailed information on the Shiraz Development Plan has been a challenge. The overall framework of this methodology is suggested for cities with visual characteristics. Abstract: Rapid urban development has posed destructive effects on the visual quality of many cities over the past few decades. Consequently, Visibility Analysis (VA) methods have been adopted to evaluate and prevent the visual influences of the development over valuable scenes. Shiraz' strategic view of the Quran Gate, in especial, is known for its remarkable landmarks, while the visual effects of the recent rapid urban growth on the view have been a matter of concern. The future of the view is even more at risk due to the lack of synergy between the urban development plan and historic preservation regulation. Consequently, this study aims to undertake a Visibility Analysis of the height regulation of the Shiraz Development Plan on the view of the Quran Gate. In this essence, two 3D models of the study area are produced based on the existing condition and the Shiraz Development Plan scenario. By choosing seventeen key viewpoints, visibility analysis of landmarks and viewpoints was conducted. The results demonstrate the destructive visual effects of the development plan on the strategic view. It is suggested that the proposed cost-efficient methodology can minimize subjective evaluation and contribute to the synergy between development and conservation plans.